Modelling the Tumor Microenvironment: Recapitulating Nano- and Micro-Scale Properties that Regulate Tumor Progression - Vahala, Danielle; Choi, Yu Suk (Frontiers in Cell and Developmental Biology, 2022)
Breast cancer remains a significant burden with 1 in 8 women affected and metastasis posing a significant challenge for patient survival. Disease progression involves remodeling of the extracellular matrix (ECM). In breast cancer, tissue stiffness increases owing to an increase in collagen production by recruited cancer-associated fibroblasts (CAFs). These stromal modifications are notable during primary tumor growth and have a dualistic action by creating a hard capsule to prevent penetration of anti-cancer therapies and forming a favorable environment for tumor progression. Remodeling of the tumor microenvironment immediately presented to cells can include changes in protein composition, concentration and structural arrangement and provides the first mechanical stimuli in the metastatic cascade. Not surprisingly, metastatic cancer cells possess the ability to mechanically adapt, and their adaptability ensures not only survival but successful invasion within altered environments. In the past decade, the importance of the microenvironment and its regulatory role in diseases have gained traction and this is evident in the shift from plastic culture to the development of novel biomaterials that mimic in vivo tissue. With these advances, elucidations can be made into how ECM remodeling and more specifically, altered cell-ECM adhesions, regulate tumor growth and cancer cell plasticity. Such enabling tools in mechanobiology will identify fundamental mechanisms in cancer progression that eventually help develop preventative and therapeutic treatment from a clinical perspective. This review will focus on current platforms engineered to mimic the micro and nano-properties of the tumor microenvironment and subsequent understanding of mechanically regulated pathways in cancer.